Further training in Germany : Continuous participation and the impact of attitudes and personality - Offerhaus, Judith [Verfasser] (Universität Bremen, 2014)
"Further training is understood as any professionally-oriented course or formalized work-related learning activity; it takes place after leaving formal education and entering the labor market. A large body of literature mainly based on cross-sectional research shows that access to and participation in further training is predominantly determined by two factors, individual level of education and occupational status. This research departs from previous work and its cross-sectional focus on socio-economic stratifiers by adopting a longitudinal modelling strategy and incorporating psychological and social psychological factors into sociological research. I focus on the case of Germany and employ data drawn from the German Socio-Economic Panel study. There are two main theoretical and empirical contributions of this dissertation. (1) Further training is viewed from the perspective of life course sociology; recurrent engagement across adulthood is phrased as prolonged educational careers which extend beyond formal schooling. Sequence and cluster analyses show that participation in training varies by educational background and previous training experience, underlining a two-fold path-dependency. Additionally, results align with the life course concept of cumulative advantage/disadvantage. Frequent and continuous participation in training is associated with higher occupational status and more favorable labor market positioning in terms of stable full-time employment; whereas training abstainers and irregular participants are over-represented among marginally and unemployed. (2) Further training is conceptualized as a function of demographics, socio-economic and work-related factors. However, this is extended by incorporating two more subjective mechanisms which subtly are at play in determining participation in training: attitudes and personality." (Author's abstract ; BIBB-Doku)
Weiterbildung in Deutschland. Kontinuierliche Teilnahme und der Einfluss von Einstellungen und Persönlichkeit.
Further Training in Germany. Continuous Participation and the Impact of Attitudes and Personality
Keywords: S 1.5 Weiterbildung; G 1.2 Arbeitsmarkt; G 1.3.2 Bildungsverhalten und -verläufe; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; Weiterbildung; Arbeitsmarkt; Bildungsverlauf; Soziale Ungleichheit